Geopolitics of the knowledge-based economy: Sami Moisio (Book Review) - Yigitcanlar, Tan (Space and Polity, 2019)
The beginning of the 21st century was marked by a major global trend—i.e., the raising of the ‘knowledge-based economies’ (Yigitcanlar & Inkinen, 2019). This important trend is induced by two concomitant factors: (a) The dramatic progress of information and communication technologies (ICTs) that disseminate at the light speed massive flows of data and information throughout the world (Yigitcanlar, 2016), and; (b) The globalisation of the world economy that exacerbates competition between firms, nations, cities/regions, and other entities (Millar & Ju-Choi, 2010; Yigitcanlar et al., 2017).